Analysis of Errors on Death Certificate for Trauma Related Death - Jun Hyuk Chang; Sun Hyu Kim; Hyeji Lee; Byungho Choi (Daehan oe'sang haghoeji, 2019)
Purpose This study was to investigate errors of death certificate (DC) issued for patients with trauma. Methods A retrospective review for DC issued after death related to trauma at a training hospital trauma center was conducted. Errors on DC were classified into major and minor errors depending on their influence on the process of selecting the cause of death (COD). All errors were compared depending on the place of issue of DC, medical doctors who wrote the DC, and the number of lines filled up for COD of DC. Results Of a total 140 DCs, average numbers of major and minor errors per DC were 0.8 and 3.7, respectively. There were a total of 2.8 errors for DCs issued at the emergency department (ED) and 5.4 errors for DCs issued beyond ED. The most common major error was more than one COD on a single line for DCs issued at the ED and incompatible casual relation between CODs for DCs issued beyond ED. The number of major errors was 0.5 for emergency physician and 0.8 for trauma surgeon and neurosurgeon. Total errors by the number of lines filled up for COD were the smallest (3.1) for two lines and the largest (6.0) for four lines. Conclusions Numbers of total errors and major errors on DCs related to trauma only were 4 and 0.8, respectively. As more CODs were written, more errors were found.